Microcutting in blueberry using branch from different positions and substrates Microestaquia em mirtileiro com diferentes porções do ramo e substratos - Pelizza T.R.* (2011)
This work was carried out aiming to evaluate the rooting capacity of microcuttings derived from different positions (median and apical) of the blueberry branches under protected environment. The blueberry (Vaccinium ashei Reade) branches cv. Climax used for this experiment were derived from the micropropagated plants. Two types of microcuttings (apical and median) and three substrates (Plantmax ® + carbonized rice rusks (1:1); Húmus Fértil ® and Vermicompound of cattle) were used. The indolbutiric acid (IBA) was applied at 2000 mg L -1 to stimulate rooting. The microcuttings were put into expanded polystyrene trays. Microcuttings from the median position showed higher percentage of surviving, higher number of leaves and shoots; however, they had higher callus formation. The number of roots is dependent on the type of microcutting and substrate used. The use of median microcuttings together with the use of the substrate Plantmax ® + carbonized rice rusks are favorable to plant production of the blueberry cv. Climax, with increases in rooting percentage and surviving cuttings, length of roots and number of leaves and shoots.